Advance institution's mission, increase student satisfaction with customer service approach. Issue 3 (25th October 2017) - Sutton, Halley
Abstract : Sharon Hoffman brought an unusual work experience to her position as assistant dean of student services at Green Mountain College: her time as a concierge at a ski resort in the mountains of Vermont, a few hours from where the campus is located. When the current president came to GMC after working for the Vermont Country Store, he wanted to address what he perceived as "customer service issues" on the campus. He wanted to change the culture of customer service, and Hoffman's experience working at the ski resort in Killington made her an ideal candidate to work there, she said.